Hubungan Safety Leadership, Safety Attitude, dan Safety Policies dengan Safety Citizenship Behavior di PT. Vale IGP Pomalaa - Sundari, Imarini; Astaginy, Niar; Ismanto, Ismanto (University of Riau Kepulauan, 2025)
This study aims to examine: (1) the effect of Safety Leadership on Safety Citizenship Behaviour among employees of PT. Vale IGP Pomalaa, (2) the influence of Safety Attitude on Safety Citizenship Behaviour in the same context, and (3) the impact of Safety Policies on Safety Citizenship Behaviour. A quantitative research approach was adopted, with data collected through observation, literature review, questionnaire distribution, and documentation. The population consisted of 1,063 employees of PT. Vale IGP Pomalaa. The sample size was determined using the Krejcie & Morgan formula, resulting in a sample of 278 respondents selected through a non-random sampling technique. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), with the analysis conducted via the SmartPLS 3.0 application. The results indicate that Safety Leadership has a positive and significant effect on Safety Citizenship Behaviour. Similarly, both Safety Attitude and Safety Policies were found to have positive and significant effects on Safety Citizenship Behaviour